If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -14n + 12 = -12n + -12 Reorder the terms: 12 + -14n = -12n + -12 Reorder the terms: 12 + -14n = -12 + -12n Solving 12 + -14n = -12 + -12n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '12n' to each side of the equation. 12 + -14n + 12n = -12 + -12n + 12n Combine like terms: -14n + 12n = -2n 12 + -2n = -12 + -12n + 12n Combine like terms: -12n + 12n = 0 12 + -2n = -12 + 0 12 + -2n = -12 Add '-12' to each side of the equation. 12 + -12 + -2n = -12 + -12 Combine like terms: 12 + -12 = 0 0 + -2n = -12 + -12 -2n = -12 + -12 Combine like terms: -12 + -12 = -24 -2n = -24 Divide each side by '-2'. n = 12 Simplifying n = 12
| 6(0.5)=Y(.25) | | 6+1=438 | | -3+9=17x-4-16x | | 3(6x-1)=-19x | | 4(w-8)=8+3w | | 9y-14y=-24-31 | | -11-(-42)=x/6 | | 4-c=20 | | 76(-2x-3)=.19x+6 | | 4y^8+15y^4+11= | | 16x^3+24x=-9 | | 16x^3+24x+9=0 | | (29-51x^3)/x | | 5x*5x=40 | | 4x-2x+7x=23 | | 1x+3=9y | | 15y+42=67y*15 | | 2/5x-10 | | 8+7=-3(3x-5) | | 2/3x-0.4y=2 | | x+23=7x+47 | | 2x-2/3+1/3=4 | | 8-11=5 | | 4(7x+10x)=3(9x-5)+20 | | 1+(3*2)=x | | 6x-8-4=10 | | 75m^2-48n^2=0 | | 5x+4x=2x+10 | | -12x^2-5x+2=0 | | -8a^2-30ab-27b^2=0 | | 8-x=2x | | -3/6+4/6=4 |